Impediments to Research: Progress and Prospects - Puriboriboon, Yongyuth; Varah, Mahaingam; Hamra, Wayne (11th International Scholars Conference, 2018)
This study’s purpose was twofold: a) to find out what progress, if any, a university located in Thailand has made in breaking down previously identified research barriers; and b) to provide practical suggestions on changes to university policies that would foster research in various departments. Data were collected from a questionnaire administered to the faculty (n = 84) of Asia-Pacific International University. Descriptive statistics and t-test were used to analyze the data. The findings showed that the university has achieved significant progress in breaking down past research barriers. The results showed that 77.3% of respondents had been published in the last five years (2013-2018) as compared to 23.9% of respondents in an earlier study conducted in 2007. Progress has been made in reducing personal barriers to research. On the other hand, institutional barriers have apparently increased. Most respondents viewed “Heavy teaching and administrative loads” to be the greatest hindrance to their research. A remaining personal barrier for all groups is “Inadequate knowledge of statistics”. These findings can be used as guidelines for administrators to foster more effective research.